Uji Aktivitas Antibakteri Ekstrak Etanol Daun Senduduk (Melastoma Malabathricum Lour.) dalam Menghambat Pertumbuhan Bakteri pada Saluran Hidung: Penelitian - Wulandari, Atika; Manurung, Dhea Amelia; Baringbing, Siska Juliana; Zain, Ulfi Khairani; Gultom, Wirda Resinta; Gultom, Endang Sulistyarini; Situmorang, Nurbaity (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the antibacterial activity of ethanol extract of senduduk leaves (Melastoma malabathricum Lour.) in inhibiting bacterial growth in the nasal passages. Senduduk plants contain bioactive compounds such as flavonoids, tannins, and saponins that have the potential as natural antibacterials. The study was conducted experimentally in vitro at the Microbiology Laboratory of the Faculty of Mathematics and Natural Sciences, State University of Medan in September 2025 using the disc diffusion method. Senduduk leaf extraction was carried out by maceration using 96% ethanol. The positive control used was the antibiotic ciprofloxacin HCl, while the negative control used DMSO (Dimethyl Sulfoxide). The growth medium used was Mueller Hinton Agar (MHA), and antibacterial activity was measured based on the diameter of the inhibition zone around the test disc. The results showed that senduduk leaf extract produced an average inhibition zone of 9.61 mm, while ciprofloxacin HCl produced an inhibition zone of around 28.45 mm, and DMSO showed no inhibition zone. This study is the basis for the development of senduduk leaves as a potential natural antibacterial ingredient in the pharmaceutical and public health fields.